Incorporating the incorporeal: The potential classification of Bitcoin as a ‘thing’ under South African common law (The Pretoria Student Law Review, 2025)
This article aims to determine whether Bitcoin could be classified as a ‘thing’ in the South African common law of things. The key motivation behind this article is to determine whether the Pandectist focus on the corporeality requirement in the classification of things is outdated in the modern, technologically driven era. Bitcoin, which is classified as a decentralised convertible virtual currency has been received positively in South Africa over the course of the last few years, as Bitcoin adoption has grown exponentially. South Africa has also seen the implementation of important regulatory reforms surrounding virtual currencies; primarily the recognition of virtual currency as a financial product and its traders as financial service providers. Given the positive reception of virtual currencies, particularly Bitcoin, in South Africa, this article explores the recognition of Bitcoin as a ‘thing’ in South Africa law, as well as the significance of this classification. From this evaluation, it will become clear that the incorporeal nature of Bitcoin poses a challenge to its common law recognition, albeit not an insurmountable one. In this regard, two arguments — the doctrinal argument and the exception argument — are proposed whereby Bitcoin could be recognised as a thing despite its incorporeality.